2020
DOI: 10.3389/fvets.2020.00496
|View full text |Cite
|
Sign up to set email alerts
|

Tea Tree Oil Prevents Mastitis-Associated Inflammation in Lipopolysaccharide-Stimulated Bovine Mammary Epithelial Cells

Abstract: The main purpose of this study was to explore the effect of tea tree oil (TTO) on lipopolysaccharide (LPS)-induced mastitis model using isolated bovine mammary epithelial cells (BMEC). This mastitis model was used to determine cellular responses to TTO and LPS on cellular cytotoxicity, mRNA abundance and cytokine production. High-throughput sequencing was used to select candidate genes, followed by functional evaluation of those genes. In the first experiment, LPS at a concentration of 200 µg/mL reduced cell p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…On the other hand, Zhi Chen et al (2020) showed that TTO can promote autolysis of E. coli and exert a remarkable inhibitory effect on LPS-induced inflammation, and the proportion of normal living mammary epithelial cells stimulated by LPS increased after treatment with TTO at a concentration (<50 μg/ml LPS). Similarly, the proportion of early apoptosis, late apoptosis, and dead cells decreased as TTO attenuated LPS-induced TNF-α and IL-6 expression [ 42 ]. Earlier studies have shown that TTO acts as a membrane permeabilizer and causes a loss of chemiosmotic control in gram-positive and gram-negative bacteria [ 43 ], and damages the membrane of C. albicans [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Zhi Chen et al (2020) showed that TTO can promote autolysis of E. coli and exert a remarkable inhibitory effect on LPS-induced inflammation, and the proportion of normal living mammary epithelial cells stimulated by LPS increased after treatment with TTO at a concentration (<50 μg/ml LPS). Similarly, the proportion of early apoptosis, late apoptosis, and dead cells decreased as TTO attenuated LPS-induced TNF-α and IL-6 expression [ 42 ]. Earlier studies have shown that TTO acts as a membrane permeabilizer and causes a loss of chemiosmotic control in gram-positive and gram-negative bacteria [ 43 ], and damages the membrane of C. albicans [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resuscitated mammary epithelial cells (MECs) were cultured in an incubator at 37°C, 5% CO 2 , and suitable humidity. The medium was changed every 48 h. The BMECs were digested with 0.25% trypsin for passaging, and the growth of cells was observed using an inverted microscope ( 26 , 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…When E. coli successfully penetrate the mammary gland through the physical barrier of the teat end, it causes an inflammatory response in the mammary gland (38,40). This colonization leads to rapid changes in the expression levels of immune-related genes, resulting in the inflammatory process (41,42). In addition, it has been reported that lncRNAs play an important role in pathogeninduced acute and chronic inflammation by regulating the expression of specific genes (43).…”
Section: Discussionmentioning
confidence: 99%